Concerns about the sustainability imbricated in social mission of organizations: the perception of social entrepreneurs from Brazil and Portugal - Estivalete, Vania de Fátima Barros; Andrade, Taís de; Costa, Vívian Flores; Faller, Lisiane Pellini (Revista de Administração da UFSM, 2016)
This study aims to investigate the perception of social entrepreneurs from Brazil and Portugal in relation to concerns about sustainability by revealing the social mission of the organizations they serve. Therefore, it was used as a methodological strategy the multiple case study, considering social projects in Brazil and Portugal. Data collection, semi-structured interviews with 11 social entrepreneurs were held, six of Brazil and five of Portugal, consolidated through a script with profile questions and about sustainability, characterized by social, environmental and economic dimensions, as well as consultations in sites, reports and documents. The data were analyzed qualitatively through content analysis procedure. The survey results suggest a predominance of concerns about the social dimension of sustainability in all analyzed enterprises, although different aspects to consider. As for the economic dimension, found themselves converging views between entrepreneurs interviewed in Brazil and Portugal, since the vast majority revealed a lack of financial resources and lack of government support. On the environmental dimension there was little evidence in the statements of the respondents.